Enhancing Entrepreneurial Skills for Disabled Individuals: Insights from Indonesia's Social Center - Asri, Melati Dewi; Salsabila, Nurvania; Dwiputrianti, Septiana; Wijayanti, Reni (Profit: Jurnal Adminsitrasi Bisnis, 2025)
This study addresses a significant gap in entrepreneurship research by focusing on enhancing entrepreneurial skills among disabled individuals at the ‘Griya Harapan Social Centre.’ Entrepreneurship is widely recognized as a pathway to economic empowerment for marginalized groups. However, disabled individuals face distinct barriers, including limited access to resources and societal stigma. This research identifies the skills gap in current training programs and proposes a comprehensive curriculum encompassing core entrepreneurial competencies, managerial, technical, and personal skills development. Utilizing a qualitative descriptive method, data were collected through in-depth interviews, observations, and document analysis. Findings reveal that while participants acquire vocational skills, critical entrepreneurial competencies such as risk-taking, innovation, financial literacy, and digital marketing remain underdeveloped. Managerial skills, including decision-making and planning, are also lacking, limiting participants’ potential for independent entrepreneurship. The proposed holistic training model is tailored to the specific needs of disabled individuals, offering practical solutions to overcome these challenges. The theoretical contribution of this research lies in its comprehensive framework for developing an inclusive entrepreneurial training model, thereby enriching the discourse on entrepreneurship and social empowerment while fostering economic and social inclusion for disabled individuals.